Analisis Yuridis Upah yang Layak Bagi Pekerja pada Usaha Kecil dan Mikro Berdasarkan Peraturan Pemerintah Nomor 36 Tahun 2021 tentang Pengupahan - Rachman Yusuf, Irnanda Munajad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the concept of a decent wage for workers in Micro and Small Enterprises and to examine the role of the state in ensuring the fulfillment of wage obligations by employers in accordance with Government Regulation Number 36 of 2021 concerning Wages. This research employs a normative juridical method with statutory, conceptual, and Constitutional Court decision approaches, particularly those emphasizing the importance of procedural and substantive justice in wage determination. The findings indicate that wage regulation for workers in Micro and Small Enterprises under Government Regulation Number 36 of 2021 does not fully reflect the concept of a just and decent wage, as it places greater emphasis on business flexibility and capacity rather than on fulfilling workers’ decent living needs. The study concludes that a decent wage for workers in Micro and Small Enterprises should be interpreted proportionally, while still guaranteeing minimum standards of workers’ welfare without neglecting business sustainability. Furthermore, the role of the state should not be limited to that of a regulator, but also as a protector and facilitator through the formulation otove policies, effective supervision, capacity-building facilitation, and participatory wage-setting mechanisms in order to achieve a fair balance between the protection of workers’ rights and the sustainability of Micro and Small Enterprises within the framework of a welfare state. Keywords: Decent Wage, Micro and Small Enterprises, Role of the State.